Evaluation of the Triggering Activity of Community-Led Total Sanitation to Eradicate Open Defecation in Nagari Tiku Utara, Agam Regency - Putri, Dewi Yusnisa (Jurnal Serambi Engineering, 2025)
Open defecation (OD) is a form of poor sanitation. OD can affect environmental health and public health. Community-led Total Sanitation (CLTS) is an approach that can be used to change community behavior by fostering a sense of disgust and shame towards OD practices so that the community can stop OD practices. This study is a form of CLTS triggering activity to eradicate OD in Nagari Tiku Utara. Evaluation of CLTS triggering activities was carried out to obtain community feedback after receiving triggering activities. This study was divided into several stages in the form of literature studies, procurement of triggering activity related to the eradication of OD practices, implementation of evaluation of triggering activity for the eradication of OD practices that have been carried out, and data analysis. Evaluation of the triggering activity was carried out using interviews and filling out questionnaires. The number of respondent samples taken was as many as the number of residents who attended the triggering activity related to the practice of eradicating OD in Nagari Tiku Utara, namely a sample of 30 respondents. The results of this study showed that the four components assessed after the triggering activities, namely community knowledge, community behavior, safe latrines components, and latrines observations, actually achieved achievements ranging from very good to sufficient.